Comparison of photoautotrophic and mixotrophic cultivation of microalgae messastrum gracile (Chlorophyceae) in alternative culture media - Sipaúba-Tavares, L. H. [UNESP]; Scardoeli-Truzzi, B. [UNESP]; Fenerick, D. C. [UNESP]; Tedesque, M. G. [UNESP] (FapUNIFESP (SciELO), 2020)
Growth and biological conditions of Messastrum gracile were evaluated to compare the effect of photoautotrophic and mixotrophic cultivation on the increase of biomass production and chemical conditions cultured in macrophyte and commercial culture media. The growth rate (k) of M. gracile was different in the culture media, higher in mixotrophic cultivation for Lemna minor culture medium, whilst to Eichhornia crassipes and NPK culture media were higher in photoautotrophic cultivation. Mean lipid contents in photoautotrophic cultivation were 8.2% biomass dry weight, whereas they reached 19% biomass dry weight in mixotrophic cultivation. Protein contents were below 48% biomass dry weight in photoautotrophic cultivation and 30% biomass dry weight in mixotrophic cultivation. Messastrum gracile cultured in macrophyte culture media (E. crassipes and L. minor) and NPK culture medium provided satisfactory results with regard to lipid and protein contents in mixotrophic and photoautotrophic cultivations, respectively. Lipid and protein contents in alternative media were higher or similar to the CHU12 commercial culture medium.
Comparação dos cultivos foto-autotrófico e mixotrófico da microalga messastrum gracile (Chlorophyceae) em meios de cultura alternativos
Keywords: Growth; Inorganic fertilizer; Macrophytes; Sugarcane molasses